Lexical Enrichment Through Cartoon: A Psycholinguistic Study on English Vocabulary Development - Ishak Bagea; Jefriyanto Saud; Dona Tihnike; Indra Tjahyadi; Achmad Naufal Irsyadi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Language acquisition is a dynamic process, especially during the formative years of childhood. This research delves into the depths of psycholinguistics to explore the effectiveness of using cartoons as a dynamic tool in enhancing lexical enrichment in the development of English vocabulary. The study aims to ascertain the influence of cartoons on the development of students' English vocabulary using psycholinguistic theory. This research adopts a qualitative approach. The data for this study pertain to the development of students' English vocabulary, with cartoons serving as the primary source of data. Data were collected through participant observation, with the researcher observing students' language acquisition and lexical mastery in the classroom. Additionally, interviews were conducted with students and English language teachers regarding the enhancement of students' English vocabulary acquisition, employing the recording technique. Once the data were collected, the researcher transcribed the speech data into written form, documenting the vocabulary acquired by students after watching cartoons. Subsequently, the data underwent reduction, classification, and analysis. The results of this study indicate several influences of cartoons on the development of students' language skills, including enhanced understanding of the English language, acquisition of new vocabulary, improved listening skills, introduction to culture and context, enjoyable learning experiences, comprehension of expressions and emotions, and the cultivation of speaking skills. Consequently, cartoons can be considered valuable learning aids, although it is advisable to use them in conjunction with more structured learning methods, such as English courses, textbooks, or tutors, to achieve more optimal learning outcomes.